MSCT assessment of blunt abdominal trauma in paediatric and adolescent patients: our experience in Hospital Tengku AMpuan Afzan (HTAA), Kuantan, Pahang - Hassan, Radhiana; Abd. Aziz, Azian; Mohd Yusof, Mubarak; Che Mohamed, Siti Kamariah; Sa'at@Yusof, Azlin; Abdul Rashid, Mohd Amran (2009)
CT scan is the diagnostic technique of choice for the evaluation of abdominal injury due to blunt trauma in hemodynamically stable children. CT scan has high sensitivity specificity and accuracy in the detection of the presence and extent of abdominal injuries. Although operative intervention in these cases were based on clinical criteria rather than imaging findings. CT information frequently increases diagnostic confidence of the surgeons and influence the success of nonoperative management in most children with solid viscus injury.